FAKTOR-FAKTOR YANG MEMPENGARUHI TINGGINYA LAJU PERTUMBUHAN DAN IMPLEMENTASI KEBIJAKAN PENDUDUK DI PROVINSI BALI - Suartha I Nyoman (PIRAMIDA, 2016)
High rate of population growth causes population problems to be huge problems that should be solved; ifdon’t’ there will be “Population Bomb”( Paul R. Ehrlich,1968). Factors affecting the rate of population growth afterconducting analysis with quantitative and qualitative descriptive research approach and statistical analysis and publicregulation theory by Edward III; in which the research object is in all Regencies/City in Bali. The rate of populationgrowth determined by the change of population dynamics as well as: fertility, mortality, and migration in BaliProvince. The rate of population growth is much higher than the national rate of population growth. Although theacquired bonus demography, in which Total Fertility Rate (TFR) has been decreasing from 2,5 to be 2,3 per womenhowever the Mortality Rate is still above one percent and migration rate level in the area of Sarbagita is very higheven reaches more than 4 percent. The effort of controlling the population through Keluarga Berencana (FamilyPlanning) is still stagnant, as the consequences of the weakness of the government regulation implementation.